The Impact of the Bahteramas Bridge Construction on the Socioeconomic Conditions of the Community in Abeli District - Renaldy, Adrian; Indriasary, Anita; Khairisa, Noor Husna; Ido, Irfan; Fitriani, Fitriani; Kumar, Shubham (Pusat Kajian Berkelanjutan UIN Sulthan Thaha Saifuddin Jambi, 2025)
The construction of the bridge connecting Abeli District and Nambo District in Kendari City has had significant impacts on the socio-economic conditions of the local community, including employment opportunities, income levels, social cohesion, and public safety. This research aims to quantitatively assess the effects of the bridge infrastructure development on these socio-economic factors in Abeli District. Data were collected through structured interviews with 156 respondents residing within a 500-meter radius of the bridge, selected via [specify sampling method, e.g., purposive or random sampling]. The collected data were analyzed using simple linear regression and descriptive statistical methods to evaluate relationships between infrastructure development and socio-economic variables. The results indicate a statistically significant positive relationship between bridge infrastructure and community social activities, with a regression coefficient of 0.421 (p < 0.05). This suggests that the bridge has facilitated stronger social ties by connecting previously separated communities across Kendari Bay, improving access, and reducing travel distances to educational facilities. Additionally, the economic analysis reveals a positive impact on community income, particularly among traders, with a regression coefficient of 0.473 (p < 0.05). This effect is attributed to increased consumption by bridge construction workers and enhanced accessibility, alongside a notable reduction in transportation expenses, including fuel costs and crossing fees.